A new kind of nonlocal symmetry for the μ‐Camassa‐Holm equation with linear dispersion. (28th October 2018) - Shi, Zhenhua; Du, Jingjing
Abstract : The μ ‐Camassa‐Holm equation with linear dispersion is a completely integrable model. In this paper, it is shown that this equation has quadratic pseudo‐potentials that allow us to construct pseudo‐potential–type nonlocal symmetries. As an application, we obtain its recursion operator by using this kind of nonlocal symmetry, and we construct a Darboux transformation for the μ ‐Camassa‐Holm equation.